Dietary risk factors for colorectal cancer in Brazil: a case control study - Angelo, Sandro Nunes; Lourenco, Gustavo J.; Magro, Daniela O.; Nascimento, Helvia; Oliveira, Rogerio A. [UNESP]; Leal, Raquel F.; Ayrizono, Maria de Lourdes S.; Fagundes, Joao J.; Coy, Claudio S. R.; Lima, Carmen S. P. (Biomed Central Ltd, 2016)
Background: High meat intake and low consumption of vegetables, fruits and whole grains have been associated with increased risk of colorectal cancer in some relevant cohort studies conducted in distinct ethnic populations. The role of the dietary pattern on the risk of sporadic colorectal adenocarcinoma (SCA) in Brazil is unknown; therefore, it was the aim of the present study. Methods: The dietary patterns of 169 patients with SCA and 101 controls were analysed by food frequency recall. Crude odds ratios were calculated and given within 95 % confidence intervals. Results: Patients reported higher average intakes of beef (32.0 +/- 1.8 versus 23.7 +/- 1.6, P = 0.0069), chicken (18.1 +/- 0.9 versus 12.2 +/- 0.8, P = 0.0002), and pork (8.9 +/- 0.9 versus 3.4 +/- 0.5, P < 0.0001). These individuals had a 1.025, 1.069, and 1.121-fold increased risk of SCA. Similar consumption of fish, vegetables, fruits and whole grains was reported by patients and controls. Conclusions: Meat consumption is greater in patients with SCA in the Brazilian population. Considering the study population-characterized by ethnic heterogeneity -, the environmental factor related to food habits may be associated with higher incidence of this disease in Brazil.
Keywords: Colorectal cancer; Dietary pattern; Lifestyle